Detangling the evolutionary developmental integration of dentate jaws: evidence that a p63 gene network regulates odontogenesis exclusive of mandible morphogenesis. Issue 5 (10th November 2016) - Raj, Muhammad T.; Boughner, Julia C.
SUMMARY: Vertebrate jaws and dentitions fit and function together, yet the genetic processes that coordinate cranial and dental morphogenesis and evolution remain poorly understood. Teeth but not jaws fail to form in the edentate p63 −/− mouse mutant, which we used here to identify genes important to odontogenesis, but not jaw morphogenesis, and that may allow dentitions to change during development and evolution without necessarily affecting the jaw skeleton. With the working hypothesis that tooth and jaw development are autonomously controlled by discreet gene regulatory networks, using gene expression microarray assays validated by quantitative reverse‐transcription PCR we contrasted expression in mandibular prominences at embryonic days (E) 10–13 of mice with normal lower jaw development but either normal ( p63 +/−, p63 +/+ ) or arrested ( p63 −/− ) tooth development. The p63 −/− mice showed significantly different expression (fold change ≥2, ≤−2; P ≤ 0.05) of several genes. Some of these are known to help regulate odontogenesis (e.g., p63, Osr2, Cldn3/4 ) and/or to be targets of p63 (e.g., Jag1/2, Fgfr2 ); other genes have no previously reported roles in odontogenesis or the p63 pathway (e.g., Fermt1, Cbln1, Pltp, Krt8 ). As expected, from E10 to E13, few genes known to regulate mandible morphogenesis differed in expression between mouse strains. This study newly links several genes to odontogenesis and/or to the p63 signaling network. We propose that these genes act in a novel odontogenic network that is exclusive of lower jaw morphogenesis, and posit that this network evolved in oral, not pharyngeal, teeth.